LEGAL STATUS OF VIRTUAL CURRENCY IN INDONESIA IN THE ABSENCE OF SPECIFIC REGULATIONS - Chang, Soonpeel (UI Scholars Hub, 2018)
Given Indonesia’s recent legal policy developments regarding cryptocurrency, it is pertinent to ask whether this new investment market, by its overall structural formation, holds any further risks to Indonesia beyond those to individual parties. This paper contends that any effective regulation of this new ecosystem requires adoption of the machinery of more fundamental concepts and a clear direction. Even if the Government’s skepticism about soundness of the cryptocurrency markets is fully justified, how best to protect the various parties in the market is a different issue, one which calls for urgent attention from policy makers, legal practitioners, the judiciary and academic researchers. In particular, given the increasing number of startup Indonesian companies that have scrambled for seats in the new market, and the large number of related criminal cases reported in other jurisdictions, often involving hacking or embezzlement, the urgency to study best policy practices cannot be stressed enough. Against this backdrop, this paper analyzes the current legal status of virtual currency, related parties and activities in Indonesia absent direct laws and regulations to protect relevant parties.